2023
DOI: 10.21203/rs.3.rs-2427284/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proportion of vitamin D deficiency in children/adolescents with type 1 diabetes: A systematic review and meta-analysis

Abstract: Background: The impact of vitamin D on type 1 diabetes has been a controversial topic in public health. Furthermore, significant differences in the proportion of vitamin D have been noted. The purpose of this systematic review was to determine the overall proportion of vitamin D deficiency in children/adolescents with type 1 diabetes (T1D). Methods: Based on six electronic databases (PubMed, Web of Science, Embase, Ovid Medline, ProQuest, and Cochrane Library), eligible studies since the databases’ inception u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…A global perspective provided by a comprehensive meta-analysis showed that vitamin D deficiency is prevalent in children and/or adolescents with T1DM. 20 This finding is consistent with the prevalence reported in our study (27%). This percentage is also comparable to the 20% reported by Al Senani et al 21 and the 14.8% reported by Giri et al 22 However, it was lower than the prevalence reported in studies conducted in Egypt (53.3%) 23 and India (63%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A global perspective provided by a comprehensive meta-analysis showed that vitamin D deficiency is prevalent in children and/or adolescents with T1DM. 20 This finding is consistent with the prevalence reported in our study (27%). This percentage is also comparable to the 20% reported by Al Senani et al 21 and the 14.8% reported by Giri et al 22 However, it was lower than the prevalence reported in studies conducted in Egypt (53.3%) 23 and India (63%).…”
Section: Discussionsupporting
confidence: 93%
“…The outcome contrast observed in relation to studies conducted on vitamin D deficiency among T1DM children and adolescent subjects in regard to the status of serum vitamin D can be explained by the variation in the intervention doses and duration. This may also be related to the variation in study design and sample size, which was evident in Yang et al, 20 who reported that the proportion of patients with vitamin D deficiency in a case-control study tended to be greater than that in other studies, which contributed to the variation in the results after vitamin D supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…This investigation strictly aligns with the PRISMA statement, with pre-registration on the PROSPERO platform (#CRD: 42022369072) ( 28 , 29 ).…”
Section: Methodsmentioning
confidence: 90%